Management of Business Processes in Industrial Enterprises from Bulgaria Along the Lines of Balanced Scorecard and QPR Process Designer – Practical Conclusions - Slavova, Petia (European Journal of Multidisciplinary Studies, 2016)
Processes generate results that the company provides to its customers. Customers outcomes and processes are connected in dependable interaction. The capacity of the company to provide results that customers expect, largely depends on how well managers or business analysts design and manage processes. A key factor to ensure sustainable achievement of the organization’s business process management in industrial enterprises from Bulgaria, which inevitably requires continuous measurement of their effectiveness. Ideally, the measurement must be linked to high company goals, to ensure that the processes are oriented towards these goals and assessed according to their contribution to achieving them. On the other side, measurements should be used to assess the performance of individual employees involved in the process. In other words, the high efficiency of the steps (taken as synonymous with the activities in the project context and modeling terminology using software tools) of processes should be rewarded. In a time when resources are more intangible, tangible shift as a tool for value creation, financial analysis of business becomes increasingly insufficient for the establishment of adequate assessment and prognosis. The new business reality provokes appearance of new methodologies to improve the management of business processes, and measuring and managing organizational performance.